A DFT study on the mechanism of photoselective catalytic reduction of 4-bromobenzaldehyde in different solvents employing an OH-defected TiO2 cluster model. Issue 40 (9th October 2017) - Gan, Hanlin; Peng, Liang; Gu, Feng Long
Abstract : A photoselective catalytic reduction mechanism of 4-bromobenzaldehyde in acetonitrile and ethanol was proposed by employing a Ti3 O9 H6 cluster to represent TiO2 surfaces. Abstract : Density functional theory calculations are employed to study the mechanism of photoselective catalytic reduction of 4-bromobenzaldehyde (4-BBA) in acetonitrile and in ethanol solvents. A totally relaxed Ti3 O9 H6 cluster model is proposed to represent titanium dioxide (TiO2 ) surfaces. The reduction selectivity of an adsorbed 4-BBA molecule on Ti3 O9 H6 has been investigated. Owing to the difference in the proton and H atom donating capabilities between explicit CH3 CN and C2 H5 OH solvent molecules, the photocatalytic reduction of 4-BBA is the debromination process in acetonitrile, whereas in ethanol it is the carbonyl reduction process. Therefore 4-BBA can be selectively reduced to benzaldehyde in acetonitrile and 4-bromobenzyl alcohol in ethanol, respectively. Our computational results have verified the reaction mechanism proposed by experiments and show that the debromination of 4-BBA would be efficient if both 4-BBA and Ti3 O9 H6 have an extra photoelectron. The Ti3 O9 H6 cluster, playing a role as a hydrogen source and a bridge to transfer photoelectrons from bulk TiO2, would have potential to be an ideal molecular model for understanding photocatalytic reactions on the TiO2 surface.